KAJIAN TAFSIR AL-QUR’AN: Telaah atas Kitab Taisirul Lathifil Mannani fi Khulashati Tafsiril Qur`an Karya Abdurrahman bin Nashir as-Sa’di - Anshory, Muhammad Isa (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Tafsir Maudhu'i is an interpretation that seeks to explain in a more focused and clear manner because the discussion is based on themes, so that the advantages of maudhu'i interpretation are dynamic, systematic, and easy to understand as a whole. As-Sa'di is a person who concentrates his knowledge in the field of